The Mote in Thine Eye': An Analysis of the Bible in Cartoon - Huw Thomas (University of Sheffield, 2021)
The targeting of religion in editorial cartoons has become a source of controversy. Particular tensions emerged following the publication of the Danish cartoons, a set of cartoons representing the Prophet Mohammed, published in Jyllands-Posten in September 2005. This research analyses cartoons from a different source, the satirical magazine Private Eye, with an eye towards the varied treatment of religion in this publication and the Jyllands-Posten cartoons. It focuses on the way the Bible features in Private Eye cartoons, and uses the semantic tool, the General Theory of Verbal Humour (GTVH), to analyse the way humour works in these cartoons, the target they aim at and the way the Bible features in the intertextual references of the reader. Analysing the targeting of such cartoons it concludes that there is a difference between the use of the Bible as a means of targeting other subject matter, as is evident in Private Eye examples, and the targeting within the Danish cartoons.